2015
DOI: 10.1353/nib.2015.0000
|View full text |Cite
|
Sign up to set email alerts
|

Patient and Family Perspectives on Respect and Dignity in the Intensive Care Unit

Abstract: Respect and dignity are central to moral life, and have a particular importance in health care settings such as the intensive care unit (ICU). We conducted 15 semistructured interviews with 21 participants during an ICU admission to explore the definition of, and specific behaviors that demonstrate, respect and dignity during treatment in the ICU. We transcribed interviews and conducted thematic qualitative analysis. Seven themes emerged that focused on what it means to be treated with respect and/or dignity: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 11 publications
0
25
0
Order By: Relevance
“…Responsiveness has been demonstrated to be a fundamental element for maintaining dignity in health care (Beach et al., ; Darby, Valentine, Murray, & De Silva, ; Lin, Tsai, & Chen, ; Nayeri et al., ) and is believed to promote patient‐centred care (NCGC, ). Previous studies have reported nurses’ caring characteristics provide dignity (Beach et al., ; Lin et al., ). Participants’ perception that their care resulted from the nurse's altruism was an important caring characteristic in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Responsiveness has been demonstrated to be a fundamental element for maintaining dignity in health care (Beach et al., ; Darby, Valentine, Murray, & De Silva, ; Lin, Tsai, & Chen, ; Nayeri et al., ) and is believed to promote patient‐centred care (NCGC, ). Previous studies have reported nurses’ caring characteristics provide dignity (Beach et al., ; Lin et al., ). Participants’ perception that their care resulted from the nurse's altruism was an important caring characteristic in our study.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its reliability, we are confident of the "ICU-RESPECT" index's face and content validity because our item development process was based on a robust, multi-method approach to defining the construct of respect in the ICU setting from the perspectives of patients, families, clinicians, and independent observers [9][10][11][12][13]. Furthermore, the concurrent validity of the scale is demonstrated by its ability to distinguish between groups, in this case, different intensive care units.…”
Section: Discussionmentioning
confidence: 99%
“…The research team developed an initial set of items for the draft instrument based on the literature, as well as qualitative analysis of the transcripts of interviews and focus groups, and direct observations, discussed in detail elsewhere [11][12][13]. Each of the specific types/sources of respect/disrespect identified by a participant or a direct observer was converted into a discrete candidate item for inclusion in a questionnaire.…”
Section: Phase 1: Development Of a Draft Instrumentmentioning
confidence: 99%
See 2 more Smart Citations